Joint Retirement of Couples: Evidence from Discontinuities in Denmark - Esteban García-Miralles; Jonathan M. Leganza (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study how social security influences the retirement behavior of couples. First, we exploit over two decades of full-population data and a discontinuity design to document sizable retirement spillovers to spouses when individuals reach pension eligibility age. Next, we explore underlying mechanisms. We find age differences within couples to be a fundamental determinant of joint retirement, which is driven by older spouses working longer. Accounting for these age differences reveals a strong gender gap, which prevails after controlling for relative earnings. Finally, in a complementary analysis we show that a reform increasing eligibility ages induces similar spillovers to spouses.
Keywords: J14; J26; D10; H55; 330; joint retirement; pension eligibility age; couples labor supply